ORGANIZATIONAL CULTURE AND LABOR RELATIONS: AN ANALYSIS OF RECRUITMENT, SELECTION, AND INTEGRATION POLICIES FOR NEW EMPLOYEES - Rosa de Oliveira, Fernando; Augusto da Silva Luiz, Victor; Santa Fé Jr., Clóvis (Revista Gênero e Interdisciplinaridade, 2026)
Organizational culture can be understood as the set of shared values, norms, and meanings that guide individuals’ behavior within the corporate environment. The general objective of this scientific article was to analyze how these cultural structures influence the processes of recruitment, selection, and integration of new employees, as well as the formation of social bonds and the construction of professional identity. The research methodology was developed through a literature review and an analysis of organizational processes related to human resource management, both especially centered on authors such as Edgar Schein and Idalberto Chiavenato, who conceptually address these themes. The study was based on the assumption that organizational culture directly impacts management practices by shaping behaviors and decision-making criteria. The results obtained indicate that processes aligned with institutional values promote engagement, cohesion, and talent retention. However, the absence of structured criteria may generate subjectivity, conflicts, and increased turnover. It is concluded that the alignment between organizational culture and human resource management is essential for building more productive and sustainable work environments.